Shift Ed : a Call to Action for Transforming K-12 Education. - Houle, David E. (SAGE Publications, 2011)
A comprehensive guide to transforming American schools Futurist David Houle and educational strategist Jeff Cobb issue a "call to action" to everyone who is concerned about education in America. He argues that reinventing our system is inevitable and we already have the information and capabilities to make the necessary changes. Shift Ed challenges us to ask the right questions, expand our vision, and take action now. The book includes an overview of the educational system and expert opinions on key areas, including: Technology and connectivity Organizational behavior Curriculum.